Adolescents and morality : a study of some moral values and dilemmas of working adolescents in the context of a changing climate of opinion - Eppel, E. M. (Emanuel Montague); Eppel, M. (May) (London ; New York : Routledge, 2006)
The groundbreaking works in The Sociology of Youth and Adolescence set of the International Library of Sociology led the way to an authoritative understanding of how social interaction moulded young people. Careful observation of vulnerable and troubled children helped the leading sociologists, whose works are included in this set, to investigate how aggression, discipline, the struggle for recognition and the need to rebel shaped the personalities of the young. These are important texts for practitioners, students and teachers in health and social welfare.
BOOK COVER; HALF TITLE; TITLE; COPYRIGHT; CONTENTS; TABLES; FOREWORD; ACKNOWLEDGEMENTS; Part I: ADOLESCENT MORALS-THE CLIMATE OF OPINION; 1. THE CLIMATE OF OPINION; Part II: CONNOTATIONS OF MORALITY; 2. THE VIEWS OF SOME ADULTS IN AUTHORITY ON THE STANDARDS AND BEHAVIOUR OF ADOLESCENTS; Part III: THE YOUNG WORKERS; 3. ATTITUDES, VALUES AND DILEMMAS OF THE YOUNG WORKERS; 4. MODELS AND VALUES OF THE YOUNG WORKERS ; 5. MORAL BELIEFS OF THE YOUNG WORKERS; 6. CONNOTATIONS OF 'GOOD' BEHAVIOUR; 7. FRUSTRATION AND AGGRESSION; 8. CONCLUSIONS AND REFLECTIONS; SELECTED BIBLIOGRAPHY; INDEX.
"First published in 1966 by Routledge and Kegan Paul Ltd"--Title page verso.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Youth -- England -- London; London (England) -- Moral conditions; Jeunesse -- Angleterre -- Londres; FAMILY & RELATIONSHIPS -- Life Stages -- Adolescence; FAMILY & RELATIONSHIPS -- Life Stages -- Teenagers; Moral conditions; Youth; England -- London